THE N-HEXANE FRACTION OF KESUM (Polygonum Minus L.) INDUCE APOPTOSIS THE LUNG EPITHELIAL CELLS OF THE RATUS NOVERGICUS THAT EXPOSED BY BENZOPYRENE - Muhamad Agus Wibowo; Basuki Bambang Purnomo; Mohammad Aris Widodo; Aulanni’am Aulanni’am (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
Kesum (Polygonum minus L.) is a popular plant and is often used as additives in many typical dishes in the West Kalimantan. These plants belong to the family Polygonaceae, and potential to use in the prevention and treatment of lung cancer. This research aimed at studying the effect of giving the n-hexane fraction of the kesum to induces of apoptosis in epithelial cells of lung tissueof the animal models that exposed by benzopyrene. research was conducted on three groups of animal models: i) the healthy group, ii) the group treated by benzopyrene 200 mg/kg, and iii) the therapy group by n-hexane fraction 100 mg/kg. The results of the study then carried measurements of lung epithelial cell apoptosis index and measurements of lung ROS levels. The results showed that n-hexane fraction able to reduce of lung ROS levels of the animal models that exposed by benzopyrene with MDA levels respectively are 5.09 ± 0.76 ppm for the healthy group, 8.44 ± 1.89 ppm for the group treated by benzopyrene, and 5.47 ± 1.76 ppm for the therapygroup. The n-hexane fraction also able to induce apoptosis of the lung epithelial cells of the animal models that exposed by benzopyrene with apoptosis index values respectively are 2.61 ± 1.98 for the healthy group, 7.41 ± 2.26 for the group treated by benzopyrene, and 16.31 ± 5.73 for the therapy group.